MENGHIBAHKAN HARTA YANG TELAH DIWASIATKAN (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 443 K/AG/2010) - WINA DEVIANTI RAMBE (PREMISE LAW JURNAL, 2016)
A will is a message from someone in the form of statement orally or written form with an object or rights to another person or an institution which is valid after the giver who makes the statements dies. From the judicial viewpoint, a will is one-sided legal action or one-sided statement. In other words, there is no achievement contract from the receiver side which can be done without the presence of receiver and it can be done in oral or written form in front of two fair witnesses. Although the testator can revoke his will as long as he is still alive, the revocation and accomplishment should be based on the prevailing regulations. The Supreme Court agrees with the Ruling of the Religious High Court, Semarang, that the will is valid and binding. Although a will is one-sided legal action, in the accomplishment when someone has given his property to someone, and he wants to give it back to another person, the revocation of the will should be firmly and clearly stated. Keywords : Hibah, Will, Property